On the Intermediate Line Region in AGNs - Adhikari, Tek P.; Różańska, Agata; Hryniewicz, Krzysztof; Czerny, Bozena; Ferland, Gary J. (Frontiers in Astronomy and Space Sciences, 2017)
In this paper we explore the intermediate line region (ILR) by using the photoionisation simulations of the gas clouds present at different radial distances from the center, corresponding to the locations from BLR out to NLR in four types of AGNs. We let for the presence of dust whenever conditions allow for dust existence. All spectral shapes are taken from the recent multi-wavelength campaigns. The cloud density decreases with distance as a power law. We found that the slope of the power law density profile does not affect the line emissivity radial profiles of major emission lines: H${β}$, He~II, Mg~II, C~III] ~and [O~III]. When the density of the cloud at the sublimation radius is as high as 10$^{11.5}$ cm$^{-3}$, the ILR should clearly be seen in the observations independently of the shape of the illuminating radiation. Moreover, our result is valid for low ionization nuclear emission regions of active galaxies.